Systematic Management of Traditional Games as Educational Media: A Multiple Case Study of Learning Quality Enhancement in Indonesian Primary Schools - Prialita, Arianti; Hanafiah, Hanafiah (Journal of Innovation and Research in Primary Education, 2025)
Traditional games represent untapped educational resources with significant potential for enhancing student learning quality, yet systematic management approaches for their integration remain underexplored in contemporary educational research. This study investigates the management of traditional games as educational media to improve learning quality in primary school settings. A qualitative multiple case study was conducted at two primary schools in West Java, Indonesia: SDN Cipanas, Citamiang Sub-district, Sukabumi City, and SDN Cimalati, Karangtengah Sub-district, Cianjur Regency. Data collection employed structured observations, in-depth interviews with principals, teachers, and students, and document analysis of curriculum materials and assessment records. Analysis followed Miles and Huberman's interactive model, applying Terry's management framework comprising planning, organizing, actuating, and controlling functions. Results demonstrated significant improvements in student learning outcomes, including 15.3% enhancement in mathematics performance through Congklak implementation and 12.7% improvement in physical coordination via Engklek activities. Student engagement scores ranged from 4.1 to 4.5 on a five-point scale across all traditional games. Qualitative findings revealed enhanced social skills, increased cooperation, and improved cultural awareness among participants. However, implementation challenges included curriculum time constraints reported by 65% of teachers and weather-dependent outdoor activity limitations. The study validates traditional games as effective educational media when systematically managed, providing a practical framework for culturally-responsive pedagogy. These findings contribute to game-based learning literature by demonstrating non-digital alternatives that simultaneously preserve cultural heritage while achieving measurable educational outcomes.